PELATIHAN PARAFRASE PADA MAHASISWA: UPAYA MENGHINDARI PLAGIARISME PADA PENULISAN KARYA ILMIAH - Uzlifatul Masruroh Isnawati; Nurul Badriyah; Titin Titin (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Students accomplishing their research project at the end of their study must write their final report projects, such as skripsi and research articles. Due to the process of those scientific papers, they should have known and understood the importance of copyright and plagiarism issues. This paper reports the community service program covering paraphrasing training to avoid plagiarism. This program was conducted in the Faculty of Economics Universitas Islam Lamongan at the beginning of the odd semester of 2021-2021. The study shows that most of the students have not been familiar with UU No. 17 in the year 2010. Further, after the students were given some practices and training on paraphrasing, it is known that the students have not practised paraphrasing activities in writing their scientific papers. Finally, this program is regarded as a meaningful activity for the students to write in advance